Development of the Potential of Extrak Lidah Mertua (Sansevieria sp) and Lemongrass (Cymbopogon Nardus) in Lowering the Number of Air Germs of Space through Humidifier Modification - AT Diana Nerawati (Journal of Global Pharma Technology, 2020)
According to Regulation of the Minister of Health No.1077 of 2011, indoor air pollution especially houses are very dangerous to human health, because in general people spend more time doing activities indoors so that the house becomes very important as a micro environment related to the risk of air pollution. Efforts to deal with indoor air pollution caused by germs need to be carried out, especially indoor air pollution the danger level is greater than outdoors. The goal is to test the decrease in germ rate in the air of the room with humidifier modification using sansevieria and lemongrass extrak. The experimental design used in the study is One Group Pretest Posttest Design. As a humidifier modification material to lower the Air Germ Number of the Room. The achievement of this goal was done using pre-experiments with the form of One Group Pre- Post Test Design. The free variables are Sansevieria extraks with concentrations of 30%, 40% and 50% and the bound variables are germ numbers. Analysis of the data used in the form of a paired t test and Anova test. The results showed that the average extrak air germs of Sansevieria and Lemongrass concentrations were 30% before treatment of 15.6 CFU/dm3 and after treatment of 3.4 CFU/dm3, while the concentration of 40% of space air germs before treatment is 19.8 CFU/dm3 and after treatment 5.6 CFU/dm3 and the concentration of 50% of space air germs before treatment is 17.2 CFU/dm3 and after treatment is 6 CFU/dm3. The result of the paired t test showed that p < 0,05, means there is a significant difference in the decrease in the number of germs before and after treatment at all conditions. Extrak Sansevieria and Lemongrass are able to lower the number of air germs of space. at extrak concentrations Sansevieria 30% and lemongrass 0.1 % the average decrease in the germ rate is 78.2%, while for concentrations 40% the average decrease in germ rate is 74.24% and the average 50% concentration decrease in the germ rate is 65.11%. Anova test results obtained that tongue in-laws extract (Sansiviera,sp) concentrations of 30% 40% and 50%, have a p value of > 0.05, which means there is no meaningful or insignificant difference.The results of this study are extrak Sansevieria sp and Cymbopogon Nardus as humidifier fluid modification at concentrations of 30%, 40% and 50% have the same effectiveness in lowering indoor air germs. Recommendations for development and trials modify sansievera and lemongrass extrak solutions with other oceans that can also absorb air pollution. Keywords: Germ numbers, Humidifier, Extrak sansieveira and cymbopogon nardus, air spaces.